Civic Campaign in Citizenship Courses to Improve the National Character of Students of the Bandung Institute of Technology (ITB) - Fauziah, Fitri Nurul; Fajrin, Elis Amani; Nurdin, Encep Syarief; Rahmat, Cece; Kurniawaty, Imas (Dinasti International Journal of Digital Business Management, 2025)
This research is motivated by the weakening spirit of nationalism among students, as reflected in low social participation, declining concern for national issues, and an increasing individualistic orientation within the university environment. In the context of globalization and digital disruption, civic education needs to evolve into an arena for active and reflective character development through innovative approaches, such as civic campaigns. This study aims to analyze the effect of implementing a civic campaign in the Civics course on improving the nationalistic character of students at the Bandung Institute of Technology (ITB). The study employed a quantitative approach, utilizing an explanatory survey method with 100 student respondents. Data were collected through a standardized questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 4 software. The results showed that the civic Campaign had a positive and significant effect on strengthening students' nationalistic character, as measured through the dimensions of national awareness, social responsibility, and active participation in community activities. A collaborative learning environment and lecturer support were also proven to play an important mediating factor in strengthening the relationship between variables. These findings confirm that the civic campaign approach can revitalize citizenship education by fostering sustainable moral and social engagement among students. The practical implications of this research lie in the need to integrate civic campaigns into the Civics curriculum to shape a young generation with a nationalistic character and a focus on social responsibility